Personal carbon allowances: Can a budget label do the trick?. (October 2018) - Marek, Ewelina; Raux, Charles; Engelmann, Dirk
Abstract: In this study, participants in a computerized experiment were asked to manage Personal Carbon Allowances (PCAs) and tokens (here an experimental currency) simultaneously and to spend their budget on either private or public transportation. They participated in four treatments, which differed with respect to the available budget. Treatments 1 and 2 served as a baseline and concerned the administration of tokens only. In treatment 3, PCAs encompassed an environmental label on the budget in favour of public transportation. This increased choices for public transportation by 12 percentage points, when comparing to treatment 2. In treatment 4, by labelling a part of the budget for public transportation, subjects increased their spending on that transport mode by 15 percentage points when comparing to treatment 2. These findings contribute to the academic and policy discussions on whether PCAs could provide an effective instrument to tackle increasing levels of pollution from transportation. Highlights: The experimental results show that PCAs could provide an effective instrument to tackle increasing levels of pollution from transportation. PCAs put a label on one's budget that makes the emissions from transportation more tangible to subjects. Introduction of PCAs evoked immediate changes in budgeting decisions that were pro-environmental. The experiment revealed that people should be able to administer two budgets simultaneously, i.e., a monetary currency and PCAs.